Increasing the efficiency of stimulation of compacted carbonate reservoirs with acid solutions based on methyl acetate - Zezekalo, Ivan; Zimin, Oleh; Laziebna, Yuliya (Eastern-European Journal of Enterprise Technologies, 2024)
The development of oil and gas deposits in compacted rocks is a promising area of development in the oil and gas industry. The object of research in this paper is the filtration properties of compacted rocks. To develop such deposits, special extraction technologies are required. Compacted carbonate rocks are easily dissolved by most acids, but for effective use, it is necessary that working solutions have very low viscosity and surface tension coefficient. Special filtration equipment has been developed for the research, which allows pumping various liquids and gases through rock samples and measuring permeability at pressures up to 1,000 bar. To determine the effectiveness of the acid solution, three groups of samples were studied: silty sandstone with clay-carbonate cement with a permeability of 0.2–0.95 mD, compacted organogenic-detrital light gray limestone with a permeability of 0.001–0.004 mD, and organogenic-detrital gray limestone with a permeability of 0.04–0.06 mD. In the course of the study, the stimulation fluid was pumped through the samples at a pressure of 200–300 bar and a temperature of 120 °C. The efficiency was determined by the change in nitrogen permeability of the samples before and after the experiments. In general, the studied stimulation fluid allowed increasing the permeability of rocks up to 3–7 times, depending on the rock and research conditions. The solution retains its reactivity for a long time and, due to its low viscosity and surface tension, penetrates deeply into the rock and significantly increases the well treatment radius compared to conventional acid treatments. The use of the developed acid solution for well stimulation will increase the efficiency of hydrocarbon production from compacted reservoirs without the use of hydraulic fracturing